Experimentally simulating the dynamics of quantum light and matter at deep-strong coupling - N. K. Langford (Nature Portfolio, 2017)
Realising deep-strong coupling phenomena for interacting light-matter systems remains an experimental challenge. Here, Langford et al. employ a circuit quantum electrodynamics chip with moderate coupling between a resonator and transmon qubit to realise digital quantum simulation of deep-strong coupling dynamics.